Magnetite: From Synthesis to Applications - Unsoy, Gozde; Gunduz, Ufuk; Oprea, Ovidiu; Ficai, Denisa; Sonmez, Maria; Radulescu, Marius; Alexie, Mihaela; Ficai, Anton (Current Topics in Medicinal Chemistry, 2015)
In this review the synthesis, functionalization and some applications of magnetite nanoparticles (MNPs) were highlighted. It is our intention to highlight the correlations between the synthesis routes, related synthesis parameters, functionalization strategies and the properties expected for the materials containing MNPs. The uses of MNPs are strongly influenced by the properties of the materials. Therefore this review is trying to discuss the applications of the magnetite and magnetite based nanomaterials by taking into account all the factors that can influence the properties of the final materials and consequently their potential applications.
Keywords: Magnetite